2020
DOI: 10.3390/biomedicines8120534
|View full text |Cite
|
Sign up to set email alerts
|

Multiple Sclerosis in a Multi-Ethnic Population in Houston, Texas: A Retrospective Analysis

Abstract: Multiple Sclerosis (MS) is a progressive neurodegenerative disease that affects more than 2 million people worldwide. Increasing knowledge about MS in different populations has advanced our understanding of disease epidemiology and variation in the natural history of MS among White and minority populations. In addition to differences in incidence, African American (AA) and Hispanic patients have greater disease burden and disability in earlier stages of disease compared to White patients. To further characteri… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 30 publications
0
5
0
Order By: Relevance
“…Importantly, there were no significant differences between the two groups with respect to demographics (smoking, body mass index, comorbidities, baseline vitamin D levels, educational attainment), age of onset, diagnostic lag, or treatment duration, suggesting that disease is inherently worse in Latin Americans ( 6 ). Conversely, a study from Texas, United States comparing non-Latin American White, Latin American, and non-Latin American Black pwMS did not find a significant difference in brain atrophy or spinal cord atrophy between groups ( 38 ). However, the number of non-Latin American White pwMS included in this study was low at 11, and thus could have been underpowered to detect differences between groups.…”
Section: Adult Ms Studiesmentioning
confidence: 93%
See 1 more Smart Citation
“…Importantly, there were no significant differences between the two groups with respect to demographics (smoking, body mass index, comorbidities, baseline vitamin D levels, educational attainment), age of onset, diagnostic lag, or treatment duration, suggesting that disease is inherently worse in Latin Americans ( 6 ). Conversely, a study from Texas, United States comparing non-Latin American White, Latin American, and non-Latin American Black pwMS did not find a significant difference in brain atrophy or spinal cord atrophy between groups ( 38 ). However, the number of non-Latin American White pwMS included in this study was low at 11, and thus could have been underpowered to detect differences between groups.…”
Section: Adult Ms Studiesmentioning
confidence: 93%
“…One study found significantly greater T2 lesion volumes in Latin American MS patients compared to non-Latin American White MS patients, and the T2 lesion volumes were correlated with expanded disability status scale (EDSS) scores in Latin American patients (6). Another study looking specifically at Latin American, non-Latin American White, and non-Latin American Black patients in Texas, United States did not find any significant differences between groups with respect to the number of T1, T2, and gadolinium-enhancing lesions at time of diagnosis, nor were there differences between groups in the number of T2 or gadoliniumenhancing lesions involving the spinal cord at diagnosis (38).…”
Section: Studies On Lesion Burden Volume and Locationmentioning
confidence: 98%
“…Since adequate MS treatment requires a comprehensive and multidisciplinary approach, the presence of these risk factors can suggest a potential increased risk of disability and disease progression in minority populations. In a previous single-center retrospective study, after adjustment for race and age, MS patients who were evaluated by a neurologist at diagnosis were found to have 60% lower odds of attaining an EDSS > 4.5 at subsequent follow-up visits compared to patients evaluated by a non-neurologist [ 47 ].…”
Section: Social Determinants Of Health and Healthcare Utilizationmentioning
confidence: 99%
“…There is wide variation in the time from the onset to the progression of SPMS [ 11 ] and some controversy regarding the clinical characteristics (initial symptoms, MRI features, disease prognosis, etc.) of both RRMS and SPMS clinical courses (phenotypes) of MS [ 11 , 12 ].…”
Section: Introductionmentioning
confidence: 99%